Pengembangan E-Book Numerasi Materi Statistika Kelas X SMA - Muallif, Mukhammad Hasan; Palupi, Evangelista Lus Windyana (Program Studi S1 Matematika UNESA, 2023)
This study aims to produce numeracy e-books that are feasible and valid in terms of content, presentation, and language and describe the practicality in terms of teacher and student response questionnaires and the effectiveness of numeracy e-books as learning media on statistics material in terms of improving pretest and posttest results. This research is an R&D research with the 4D method (Define, Design, Develop, Disseminate), only until the development stage (develop) but still tested limitedly to students. The Numeracy E-book developed was tested on students of class X-3 SMA Negeri 12 Surabaya. Based on the results of the research that has been done, the development of E-book Numeration on statistics material obtained content validation results of 86% and construct validation results of 87% with a very valid category and feasible to use. In the aspect of practicality, the results of very positive responses from students and teachers were 96% with a very practical category. The effectiveness aspect based on the pretest and posttest results obtained an average n-gain score of 0.71 with a high category. Thus, overall this study can be concluded that the Numeracy E-book developed is feasible to use as a learning media on statistics material.